An eclectic theory of the choice of international entry mode - Hill, Charles W. L.; Hwang, Peter; Kim, W. Chan (Strategic Management Journal, 1990)
Abstract The choice of entry mode into a foreign market has a major impact on the success of a firm's international operations. However, the existing literature on the entry mode decision has either presented a list of considerations without identifying underlying constructs, or treated each entry decision in isolation. Here, a unifying framework is developed. This framework identifies three underlying constructs that influence the entry mode decision. These constructs are linked to considerations that have been previously discussed in the literature. It is argued that a firm's choice of entry mode depends on the strategic relationship the firm envisages between operations in different countries. A particular entry decision cannot be viewed in isolation. It must be considered in relation to the overall strategic posture of the firm. Further, the paper argues that different variables often suggest different entry modes, and that resolving these differences involves accepting trade‐offs.